Effects of Alcohol Use on Patient Retention in HIV Care in East Africa - Monroy, Alexa; Goodrich, Suzanne; Brown, Steven A.; Balanos, Theofanis; Bakoyannis, Giorgos; Diero, Lameck; Byakwaga, Helen; Muyindike, Winnie; Kanyesigye, Michael; Aluda, Maurice; Lewis‑Kulzer, Jayne; Yiannoutsos, Constantin; et al. (AIDS and Behavior, 2024)
We sought to investigate the association between hazardous alcohol use and gaps in care for people living with HIV over a long-term follow-up period. Adults who had participated in our previously published Phase I study of hazardous alcohol use at HIV programs in Kenya and Uganda were eligible at their 42 to 48-month follow-up visit. Those who re-enrolled were followed for an additional ~ 12 months. Hazardous alcohol use behavior was measured using the Alcohol Use Disorders Identification Test (AUDIT) tool. DE identified clinical data were used to assess gaps in care (defined as failure to return to clinic within 60 days after a missed visit). The proportion of patients experiencing a gap in care at a specific time point was based on a nonparametric moment-based estimator. A semiparametric Cox proportional hazard model was used to determine the association between hazardous alcohol use at enrollment in Phase I (AUDIT score ≥ 8) and gaps in care. Of the 731 study-eligible participants from Phase I, 5.5% had died, 10.1% were lost to follow-up, 39.5% transferred, 7.5% declined/not approached, and 37.3% were enrolled. Phase II participants were older, had less hazardous drinking and had a lower WHO clinical stage than those not re-enrolled. Hazardous drinking in the re-enrolled was associated with a Hazard Ratio (HR) of 1.88 [p-value = 0.016] for a gap in care. Thus, hazardous alcohol use at baseline was associated with an increased risk of experiencing a gap in care and presents an early target for intervention.
Keywords: Gap in care; Alcohol; East Africa; HIV